63-Year-Old Male with Gastric Outlet Obstruction. (14th September 2014) - Khalsa, Bhavraj; Rudersdorf, Patrick; Dave, Dattesh; Smith, Brian R.; Lall, Chandana
Abstract : We describe a case of a 63-year-old male with complicated Bouveret's syndrome, both in its presentation and in its management. Bouveret's syndrome is a rare cause of gastric outlet obstruction resulting from mechanical obstruction from gallstones at the pyloroduodenal segment. As Bouveret's syndrome can be a diagnostic and therapeutic challenge for clinicians, we aim to identify clinical and radiologic pearls that can lower the threshold for the diagnosis of Bouveret's syndrome.